The Complexome of Dehalococcoides mccartyi Reveals Its Organohalide Respiration-Complex Is Modular - Seidel, Katja; Kühnert, Joana; Adrian, Lorenz (Frontiers in Microbiology, 2018)
Dehalococcoides mccartyi strain CBDB1 is a slow growing strictly anaerobic microorganism dependent on halogenated compounds as terminal electron acceptor for anaerobic respiration. Indications have been described that the membrane-bound proteinaceous organohalide respiration complex of strain CBDB1 is functional without quinone-mediated electron transfer. We here study this multi-subunit protein complex in depth in regard to participating protein subunits and interactions between the subunits using blue native gel electrophoresis coupled to mass spectrometric label-free protein quantification. Applying three different solubilization modes to detach the respiration complex from the membrane we describe different solubilization snapshots of the organohalide respiration complex. The results demonstrate the existence of a two-subunit hydrogenase module loosely binding to the rest of the complex, tight binding of the subunit HupX to OmeA and OmeB, predicted to be the two subunits of a molybdopterin-binding redox subcomplex, to form a second module, and the presence of two distinct reductive dehalogenase module variants with different sizes. In our data we obtained biochemical evidence for the specificity between a reductive dehalogenase RdhA (CbdbA80) and its membrane anchor protein RdhB (CbdbB3). We also observed weak interactions between the reductive dehalogenase and the hydrogenase module suggesting a not yet recognized contact surface between these two modules. Especially an interaction between the two integral membrane subunits OmeB and RdhB seems to promote the integrity of the complex. With the different solubilization strengths we observe successive disintegration of the complex into its subunits. The observed architecture would allow the association of different reductive dehalogenase modules RdhA/RdhB with the other two protein complex modules when the strain is growing on different electron acceptors. In the search for other respiratory complexes in strain CBDB1 the remarkable result is not the detection of a standard ATPase but the absence of any other abundant membrane complex although an 11-subunit version of complex I (Nuo) is encoded in the genome.